Beginning Amazon Web Services with Node.js - Shackelford, Adam (Expert's voice in Web development., 2015)
Beginning Amazon Web Services with Node.js teaches any novice Node.js developer to configure, deploy, and maintain scalable small to large scale Node.js applications in Amazon Web Services. Hosting a Node.js application in a production environment usually means turning to PaaS hosting, but this approach brings problems. Deploying Node.js directly to AWS solves the problems you encounter in these situations, enabling you to cut out the middle man. You will begin with a basic RESTful web service in Node.js, using the popular Express.js framework, pre-built and ready to run in your local environment. You will be introduced to the most powerful tools in AWS, and learn how to configure your project to take advantage of them. You will be guided through the steps of getting the various key components to work together on AWS. Through code samples using the AWS JavaScript SDK and tutorials in the AWS console, you will gain the knowledge to incorporate secure user authentication, server auto-scaling, a load balancer, CDN, customized caching behavior, and outage monitoring. Node.js is single-threaded, and designed to run high input / high output applications, making it ideal for the cloud environment. If your main task is handling a high volume of requests over HTTP / the web, it will scale very well in proportion to the computing power you allocate to it. Amazon Web Services offers a broad set of services that help organizations move faster, lower costs, and scale applications. Trusted by the largest enterprises and start-ups alike, AWS powers a wide variety of workloads across a broad spectrum. If leveraged properly, you can build a Node.js app on AWS which can automatically power itself up to handle a massive volume of traffic, and then scale back down to a lighter configuration when user demand has dropped. Amazon Web Services offers a broad set of services that help organizations move faster, lower costs, and scale applications. Get started with Node.js and AWS using this book today.